2009
DOI: 10.1186/1471-2148-9-129
|View full text |Cite
|
Sign up to set email alerts
|

You can't always get what you want: size assortative mating by mutual mate choice as a resolution of sexual conflict

Abstract: Background: Assortative mating patterns for mate quality traits like body size are often observed in nature. However, the underlying mechanisms that cause assortative mating patterns are less well known. Sexual selection is one important explanation for assortment, suggesting that i) one (usually the female) or both sexes could show preferences for mates of similar size or ii) mutual mate choice could resolve sexual conflict over quality traits into assortment. We tested these hypotheses experimentally in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 50 publications
(50 reference statements)
5
65
0
Order By: Relevance
“…The result confirms the immense role of female body size as the mate choice criterion in male P. taeniatus found in a previous study [32]. Body size is correlated with female fecundity in P. taeniatus ( [32]; T.T., T.C.M.B., N. Henning & H. Kullmann, 2009, unpublished data), and thus closely related to fitness. The particular importance of female body size in male mate choice is therefore not surprising.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The result confirms the immense role of female body size as the mate choice criterion in male P. taeniatus found in a previous study [32]. Body size is correlated with female fecundity in P. taeniatus ( [32]; T.T., T.C.M.B., N. Henning & H. Kullmann, 2009, unpublished data), and thus closely related to fitness. The particular importance of female body size in male mate choice is therefore not surprising.…”
Section: Discussionsupporting
confidence: 89%
“…Previous experiments revealed that males and females of P. taeniatus use body size (an ornamental trait) as well as genetic relatedness (a compatibility criterion) in mate choice, when these criteria were tested independently from each other: as in other cichlids [33][34][35][36][37], both sexes preferred large individuals [32]. Mating with large individuals provides several indirect and direct benefits in biparental cichlids, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Partial isolation between ecotypes also enables natural selection to enhance existing differences between alternative morphs (Pfennig et al 2010). Size assortative mating is a widespread phenomenon in many species (Crespi 1989, Erlandsson & Rolán-Alvarez 1998, Hollander et al 2005, Baldauf et al 2009). In the case of Melarhaphe neritoides, the morpho types meet and probably copulate in situ with specimens of the same morphotype, increasing the likelihood that the eggs and larvae released combine genes from the mother and father putatively adapted to the same microhabitat conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the covered distance was measured as a proxy for activity and acclimatisation. Among cichlids, males are the predominant sex in substrate interaction, especially in the context of nest building (Baldauf 2006, Mendonça et al 2010, Schaedelin & Taborsky 2010. Thus, one would predict that male P. taeniatus show a stronger response than females to sand-treated water.…”
Section: Introductionmentioning
confidence: 99%
“…It has a well-developed sense of smell and is able to discriminate between its own and familiar kin chemical cues ). Also, P. taeniatus males interact intensively with available sand and construct sand piles in front of their breeding caves (Baldauf 2006).…”
Section: Introductionmentioning
confidence: 99%